Avaliação da solução e desenvolvimento inicial de cafeeiro conilon em decorrência da aplicação de água residuária de suinocultura - Brumat, Ana Elisa Lyra (2018)
Fertilizer economics, reduction of negative impacts on the environment and preservation of good quality water sources have been presented as important factors due to the use of wastewater in agricultural crops. However, despite the aforementioned benefits